AUTOMATION OF SPREADSHEET READING WITH ARTIFICIAL INTELLIGENCE INTEGRATION: DEVELOPMENT OF THE SHEET2PROMPT API APPLICATION - de Matos, Gabriel Luciano Alparone; Santana, Keury Ryan de Souza; dos Santos, Ricardo Marciano; Boente, Alfredo Nazareno Pereira; Ferreira, Vinícius Marques da Silva; de Carvalho, Miguel Gabriel P; Moreno, Adalgiza Mafra; Boente, Juan Gabriel Pires (Seven Editora, 2025)
This article presents the development of a web application called Sheet2Prompt API, designed to automate the reading of Google Sheets spreadsheets and integrate with artificial intelligence (AI) models for generating summaries and automated responses. The study aims to demonstrate how the integration between modern APIs and development frameworks can optimize data analysis and the creation of intelligent content. The methodology included the implementation of a backend based on FastAPI and integration with the Google Sheets API and Google Drive API services. The theoretical foundation is based on authors such as Ferreira (2025), Boente (2025), and Dos Santos (2020; 2025), who discuss the importance of automation, human-computer interaction, and adaptive logic in the context of applied AI. The results demonstrated that the developed system was able to perform accurate readings and generate coherent responses, validating the proposed efficiency of the architecture. It is concluded that the application represents an advance in the use of AI for task automation and can be expanded to different business and educational contexts.DOI: https://doi.org/10.56238/sevened2025.036-105